Pendidikan Bela Negara di dalam Kurikulum Pendidikan di Indonesia - Zainal Muhtar; Yanti Yulianti; Hanang Hanafiah (Program Pascasarjana, Universitas Islam Bunga Bangsa Cirebon, 2021)
Indonesia is a developing country that is still trying to improve the quality of education. The quality of education is a focus that needs to be considered by the government and the elements society in advancing the Indonesia nation. Education is something that is related to human development. The process cannot be separated from the psychological, human, and environmental. This study aims to determine of how the implementation of state defense education in Universitas Pertahanan curriculum is applied. The research method used is library research. The technique of this method is to collecting some reading references that are relevant to the studied problems. The literature study method was also involved in this study to support the results. The results of this study prove the needs for state defense education for students as the nation’s next generation should receive an attention from the policy makers such as the government and education environment. The various threats that will be faced are not only from military, yet it become more complex. It can be worried as it can erode the student’s senses of nationalism. The role of the government and educators is important to provide broad opportunities for the students to develop their knowledge in innovation and creativity. The students that can develop their knowledge hopefully can make proud of their country and the nation. Packaging in providing state defense education for students is need to be more innovative, in addition the students are able to understand deeply about defending their state and the importance of a sense of the nationalism to strengthen their state sovereignty. ABSTRAK Indonesia merupakan negara berkembang yang masih berusaha dalam meningkatkan kualitas Pendidikan. Kualitas Pendidikan merupakan fokus yang perlu diperhatikan oleh pemerintah serta elemen masyarakat dalam memajukan Bangsa Indonesia. Pendidikan adalah suatu hal yang terkait dengan perkembangan manusia. Prosesnya tidak terlepas dari psikologis, manusia, dan lingkungan. Penelitian ini bertujuan sejauh mana implementasi Pendidikan bela negara di dalam kurikulum Universitas Pertahanan diterapkan. Metode penelitian yang digunakan adalah library research, yaitu teknik pengumpulan referensi bacaan yang relevan dengan permasalahan yang diteliti. Metode studi literatur juga dilibatkan dalam penelitian ini untuk mendukung hasil penelitian. Hasil dari penelitian ini membuktikan kebutuhan Pendidikan bela negara untuk kalangan pelajar sebagai generasi penerus bangsa seharusnya mendapat perhatian dari pemangku kebijakan dari lingkungan pemerintah dan pendidikan. Berbagai ancaman yang dihadapi tidak hanya militer namun semakin kompleks sehingga dikhawatirkan dapat mengikis rasa nasionalisme pelajar. Peran pemerintah dan pendidik penting untuk memberikan kesempatan luas pada pelajar dalam mengembangkan ilmunya secara inovasi dan kretivitas, sehingga pelajar yang dapat mengembangkan ilmunya akan membanggakan negara dan mengharumkan nama bangsa dengan hal positif. Pengemasan dalam pemberian Pendidikan bela negara pada pelajar perlu lebih inovatif supaya pelajar mampu memahami lebih mendalam mengenai bela negara dan pentingnya rasa nasionalisme untuk memperkuat kedaulatan negara.